2012
DOI: 10.1080/02701367.2012.10599862
|View full text |Cite
|
Sign up to set email alerts
|

The Nature, Occurring Contexts, and Psychological Implications of Weight-Related Teasing in Urban Physical Education Programs

Abstract: This study examined the nature, occurring contexts, and psychological implications of weight-related teasing in urban physical education programs. Semistructured interviews were conducted with 47 participants from a large urban school district. Data were analyzed using inductive analysis and constant comparisons. Most overweight adolescents experienced many different types of teasing in physical education. Victims of teasing felt hurt and experienced uncomfortable feelings due to social comparisons. Overweight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0
44

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(67 citation statements)
references
References 37 publications
0
23
0
44
Order By: Relevance
“…Experts working in eating disorders or related fields have called for multiple policy interventions and regulations, including efforts to achieve equitable treatment and insurance coverage for eating disorders [24], implement school-based screening for eating disorders [25,26], place government restrictions on access to over-the-counter drugs and supplements for weight control by youths [27], require policies to address eating disorders in college athletic programs [28], curtail weight-related mistreatment and bullying among youth in schools [19,21,23,29,30], and implement legal protections against weight discrimination [31,32]. Fostering political will to trigger government actions in these areas will require increased and strategic advocacy efforts to prioritize eating disorders on policy agendas [33].…”
Section: Introductionmentioning
confidence: 99%
“…Experts working in eating disorders or related fields have called for multiple policy interventions and regulations, including efforts to achieve equitable treatment and insurance coverage for eating disorders [24], implement school-based screening for eating disorders [25,26], place government restrictions on access to over-the-counter drugs and supplements for weight control by youths [27], require policies to address eating disorders in college athletic programs [28], curtail weight-related mistreatment and bullying among youth in schools [19,21,23,29,30], and implement legal protections against weight discrimination [31,32]. Fostering political will to trigger government actions in these areas will require increased and strategic advocacy efforts to prioritize eating disorders on policy agendas [33].…”
Section: Introductionmentioning
confidence: 99%
“…This study was part of a larger initiative . The larger study was designed to examine overweight adolescents' teasing experience, coping mechanisms against teasing, and perceptions of PE teachers' caring behaviors, and their parents' perceptions of PE and supportive behaviors.…”
Section: Methodsmentioning
confidence: 99%
“…Students who are overweight or obese are often teased in school due to their body weight and size . As a result of being teased, these students who are overweight or obese can experience psychological and emotional damage, such as feeling hurt and discomfort, being sensitive to others' comments, and exhibiting learned helplessness .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, in a qualitative study of weight-related teasing experienced by 11-to 19-year-olds classified as overweight or obese, Li and Rukavina (2012b) reported that 55 percent of the time the physical education teachers were aware that the student was being teased, yet the teachers' responses were quite varied and often unsupportive. For example, Sometimes teachers just ignored it… Sometimes teachers even laughed at teasing comments and this hurt overweight students more.…”
Section: Obesity Bias Stigma and Physical Activity Miseducationmentioning
confidence: 97%